ASSESSMENT OF THE MINISTRY OF INTERNAL AFFAIRS SECURITY AND EMERGENCIES COORDINATION CENTERS (GAMERs) AS A CRISIS MANAGEMENT MODEL - MEHMET ÖZEL (Fırat University, 2019)
In today's world with increasing threat and danger perception, various ways and methods as well as different organizational models are tried to be developed in order to fight crises faced effectively. In Turkey the procedures and principles related to crisis management are also embraced via the Prime Ministry Crisis Management Center Regulations which came in to force on 30.09.1996. However, as the said regulation is removed from force in 2011, there have been some inadequacies incurring regarding organization and coordination related to the security and emergencies like terror events, fire, widespread violence acts, heavy economical crises, cyber attacks, energy supply security, actions threatening national security. In order to remove such inadequacies related to its field of duty, conduct the related services security based emergencies effectively country-wide,provide effective cooperation and coordinationbetween Ministry central units and institutions serving in security and public order the Ministry of Internal Affairs have established Security and Emergencies Coordination Centers (GAMERs) in Ministry headquarters and provinces. In the study, the functionality and effectiveness of the GAMERs organization is tried to be discussed, which is stated to be established by the Ministry of Internal Affairs via an integrated management understanding in security and emergencies. For this purpose, the structure and functions of GAMERs and the cadre and location issues have been discussed. And by taking the crisis management approach in Turkey into account, this organization model has been studied with regard to its effectiveness in terms of security and preparedness for emergencies, response and recovery, the functioning of cooperation and coordination between the relevant organizations, competence in terms of cadre and location